All-Russian Scientific Conference From “Spectacle Plays” to Film Comedies: The History of Homo Ridens / Всероссийская научная конференция «От “позорищных игр” до кинокомедий: история человека смеющегося» - EVALLYO VIOLETTA D. / ЭВАЛЛЬЁ В.Д. (Наука телевидения, 2022)
The article reviews the reports presented at the All-Russian Scientific Conference From “spectacle plays”1 to film comedies: The history of Homo Ridens, which was organized by the State Institute for Art Studies and the GITR Film and Television School on June 2–3, 2022. The event focused on comprehension of the historical development of laughter culture, introduction of trusted research concepts, disclosure of new facts and archival materials, and revealing the relationship between the comic, its intensity and semantics in postmodernist aesthetics. The following key areas were proposed: fundamental problems of aesthetics, cultural studies, and art criticism; genre and stylistic varieties of comedy; circulation of laughter culture in film, television and other screen arts and in the Internet environment; transformations of representation of comic, laughter, and humor in the historical context; provocation, deconstruction, and citation in comics. The reports were divided into two groups: “Komos & ode: The laughter culture of Europe” and “Deconstruction—meaning—reality.” The results of the conference showed the polyvalence of comic existence, the absence of unified ways of achieving aesthetic flawlessness of the genre, and its formcontaining aspects. В данной статье представлен обзор докладов, прозвучавших на Всероссийской научной конференции «От “позорищных игр” до кинокомедий: история человека смеющегося» 2–3 июня 2022, организованной Государственным институтом искусствознания и Институтом кино и телевидения (ГИТР). Целью мероприятия стали: осмысление исторического развития смеховой культуры, знакомство с авторитетными исследовательскими концепциями, обнародование новых фактов и архивных материалов, выявление соотношения комического, его интенсивности и семантики в контексте эстетики постмодернизма. Организаторами данной конференции были предложены ключевые направления, такие как фундаментальные проблемы эстетики, культурологии, искусствоведения; жанровые и стилистические разновидности комедии; циркуляция смеховой культуры в кино-, теле- и других экранных искусствах, в интернет-среде; трансформации репрезентации комического, смеха, юмора в историческом контексте; провоцирование, деконструкция, цитирование в комическом. Доклады были разделены на две группы: «Komos & ode: смеховая культура Европы» и «Деконструкция — смысл — реальность». Результаты конференции показали поливариантность существования комического начала, отсутствие единых способов достижения эстетической безупречности жанра и его формосодержательных аспектов.